Implications of the 9 July 1956 MS ∼ 7.2 Amorgos Earthquake for Tsunami Hazard in the Aegean - Nikos Kalligeris; Costas Synolakis; Philip England; James Jackson; Richard Walker (Geophysical Research Letters)
Abstract The 9 July 1956 Amorgos earthquake was followed by sea waves that affected a large part of the southern Aegean Sea and, in places, were higher than 10 m. Previous analyses of this event concluded that waves generated directly by co‐seismic displacement of the seafloor were small in comparison with those caused indirectly by localized submarine landsliding. Seismological and geodetic evidence, combined with marine geophysical and submarine surveys, indicate that coseismic seafloor displacements exceeded by an order of magnitude those assumed in previous studies. Detailed calculations of runup are possible for 25 sites; with the exception of one island, these agree with observations to within uncertainty, suggesting that co‐seismic displacement of the seafloor was the principal cause of the 1956 tsunami. Scenarios of tsunami hazard from future earthquakes in the Aegean should take into account the large ratio of displacement to fault length in this earthquake.